A context-specific mediating schema approach for information exchange between heterogeneous hospital systems. (12th April 2007) - Sarnikar, Surendra; Gupta, Amar
Secure and seamless exchange of electronic patient-care information among heterogeneous interoperable systems is an important goal for future healthcare information systems. However, fast and efficient exchange of information between heterogeneous healthcare systems is inhibited by the variations in the data models used to define patient-care records, and the prohibitive costs associated with standardisation and software upgrades. In this paper, we analyse the factors impeding the adoption of interoperable healthcare systems and propose the use of a mediating schema-based approach that can enable interoperability and also minimise the impact of the impeding factors. The proposed mechanism uses context-specific mediating schemas for data translation and can enable the seamless exchange of electronic patient-care records between different healthcare systems. Our approach builds on existing technologies and is specifically adapted to the healthcare context. We illustrate the viability of our approach using a scenario relating to pre-hospital to hospital information exchange.